Strategi Terkini dalam Literasi Keuangan dan Edukasi Produk Perbankan Syariah untuk Mendorong Kemandirian Ekonomi Santri - Hamidah; Nurjali; Al-Munip (SiNORA, 2025)
The economic independence of pesantrens has become a strategic aspect in the development of community-based religious economy in Indonesia. As the next generation, santris play a crucial role in achieving this independence through the mastery of financial literacy and understanding of Islamic banking products. This study aims to evaluate the latest strategies implemented to enhance financial literacy and education on Islamic banking products for santris, as well as their impact on the economic independence of pesantrens. The research employs a descriptive qualitative method, with data collected through in-depth interviews, participatory observation, and documentation studies. The findings indicate that a combination of interactive training, mini bank simulations within pesantrens, and the utilization of digital technology effectively improves the knowledge, skills, and financial behavior of santris. Interactive training facilitates the development of critical thinking and financial decision-making skills, mini bank simulations provide practical experience in managing Islamic banking products, and digital technology expands access to information while supporting flexible learning. This holistic approach not only strengthens santris’ financial literacy but also fosters sustainable economic independence for pesantrens, equipping santris with adaptive, ethical, and productive financial competencies.